Ensuring competence of essential skills (ECOES): clinical examination for final year medical students - Faisal Waseem Ismail; Ahmed, Rashida; Khan, Sadaf; Sara Shakil (Journal of the Pakistan Medical Association, 2023)
Objective: To ensure competence of essential skills of final year medical students in clinical examination by identifying essential skills and by revisiting and practising them before the examination. Method: The cross-sectional study was conducted at the Aga Khan University, Karachi, from February to November, 2019, and comprised final year medical students and internal examiners from various academic disciplines. An overview of the organizational context, exam structure and process was noted. Results: There were 96 medical students. The four key areas highlighted were development of the list of essential skills across five years of undergraduate medical curriculum with consensus from all disciplines, student motivation for attendance in practice sessions, unfamiliarity of examiners with the assessment tool, and the need for capacity-building. The key areas were based on the feedback received from all the stakeholders, and post-hoc analysis. Conclusion: This form of assessment would enable a thorough analysis of the preparedness of the students to function as independent physicians as undifferentiated doctor at the start of their careers as interns, and improve the quality of subsequent exams based on feedback and suggestions of faculty and students. Key Words: Clinical skills, Competency-based medical education, Undergraduate medical education, Final year medical students.